2013
DOI: 10.1080/14680629.2013.779306
|View full text |Cite
|
Sign up to set email alerts
|

The role of ettringite in the deterioration of artificial lime stabilised soils: a microstructural study

Abstract: ABSTRACT. The formation of ettringite has been defined as a major failure mechanism of lime stabilised cohesive soils. It can result in both disruptive volumetric changes and loss of mechanical strength. The mechanisms of its formation and the role it plays in deleterious processes are complex. This paper reports the dimensional and strength changes of a range of artificial lime stabilised cohesive soils subject to two swell test procedures: the UK linear CBR swell test (BS1924-2, BSI 1990) and the European ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…9(e)). Similar needle structure has also been observed in previous studies where other sulfate-rich soils were stabilized by calcium-based stabilizers (Buttress et al, 2013;Celik and Nalbantoglu, 2013). These needle structures are too small (about 0.1-0.5 μm) and scattered to be detected by EDX, but they are distinguishable enough to show the formation of ettringite nevertheless by SEM.…”
Section: Microstructural and Mineralogical Characterization Of Swellisupporting
confidence: 73%
See 1 more Smart Citation
“…9(e)). Similar needle structure has also been observed in previous studies where other sulfate-rich soils were stabilized by calcium-based stabilizers (Buttress et al, 2013;Celik and Nalbantoglu, 2013). These needle structures are too small (about 0.1-0.5 μm) and scattered to be detected by EDX, but they are distinguishable enough to show the formation of ettringite nevertheless by SEM.…”
Section: Microstructural and Mineralogical Characterization Of Swellisupporting
confidence: 73%
“…Metakaolin was mixed with the alkaline activator for 30 min and then poured into the prepared sulfate-rich soils with extra water to reach the predetermined OWC values in Table 1. As reported in prior work, 3 to 6 wt.% of lime was used to stabilize sulfate-rich soils, which can significantly improve the mechanical properties, but the stabilized soils showed appreciable swelling (Chen et al, 2005;Buttress et al, 2013;Celik and Nalbantoglu, 2013); and 5 to 20 wt.% Portland cement is normally used for soil stabilization. To provide a baseline for assessing the effectiveness of MKG as a sulfate-rich soil stabilizer, soil samples stabilized with 4% lime and 5% cement were prepared as two control groups, besides unstabilized soil as another one.…”
Section: Geopolymer Synthesis and Soil Stabilizationmentioning
confidence: 98%
“…Samples were glued with a Leit-C conductive carbon cement and allowed for 48 h to dry prior to analysis. The samples were put in a FEI QUANTA FEG 650 SEM Unit at a chamber pressure of about 9.5 × 10 −7 Torr and an accelerating voltage of 5–20 kV [ 57 ]. The micrographs were taken at varying levels of the stage at 10–20 mm depending on the size of the sample.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the montmorillonite mix, the clay and sulfate content were fixed and the mix ratio adjusted for the amount of binder required by reducing the percentage sand. Fluorescence (XRF) has been presented previously in [14].…”
Section: Methodsmentioning
confidence: 99%
“…However, UK practioners have little experience of using this test as historically, the soaked CBR test has been used [13]. Previous work has shown that there are significant differences in a soils swelling response when subjected to EN13286-49 compared to BS1924-2 [14].…”
Section: Introductionmentioning
confidence: 99%